2023
DOI: 10.3390/molecules28155794
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Biodegradable Surfactants from Orange Peel for Oil Spill Remediation

Abstract: Oil spill remediation plays a vital role in mitigating the environmental impacts caused by oil spills. The chemical method is one of the widely recognized approaches in chemical surfactants. However, the most commonly used chemical surfactants are toxic and non-biodegradable. Herein, two biocompatible and biodegradable surfactants were synthesized from orange peel using the ionic liquid 1-butyl-3-methylimidazolium chloride (BMIMCl) and organic solvent dimethylacetamide (CH3CN(CH3)2) as reaction media. The acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Similar results were found in the previous research, indicating that the micellar mechanism and dispersion efficacy were improved by the synergistic impact of various surfactant agents (such as cationic, nonionic, anionic, and ionic liquids-based surfactants) . The published research also confirmed this; developed dispersants with reduced CMC produced more extraordinary oil spill dispersant performance. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were found in the previous research, indicating that the micellar mechanism and dispersion efficacy were improved by the synergistic impact of various surfactant agents (such as cationic, nonionic, anionic, and ionic liquids-based surfactants) . The published research also confirmed this; developed dispersants with reduced CMC produced more extraordinary oil spill dispersant performance. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…27 The published research also confirmed this; developed dispersants with reduced CMC produced more extraordinary oil spill dispersant performance. 3,15 3.2. Dispersion Effectiveness of the Selected Formulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water-soluble polymers used in polymer flooding are, by themselves, anionic surfactants [ 71 , 72 ]. The propagation of surfactants in the reservoir reduces the surface tension [ 71 , 72 , 73 , 74 , 75 , 76 ]. If the polymer solution contains more surfactant additives, the resulting complex of polymer molecules and surfactants has a molecular weight greater than the molecular weight of the polymer and, therefore, a higher-viscosity polymer solution.…”
Section: Polymer Flooding—field Scalementioning
confidence: 99%